Taking advantage og organelle genomes in plant breeding: an integrated approach = Aprovechando los genomas de las organelas en el mejoramiento genético de plantas: un enfoque integrado - Colombo, Noemi (Sociedad Argentina de Genética, 2019)
Plant cells carry their genetic information in three compartments: the nucleus, the plastids and the mitochondria. In last years, next-generation sequencing has allowed the development of genomic databases, which are increasingly improving our knowledge about the role of nuclear and cytoplasmic genes as well as their interactions in plant development. However, most plant breeding efforts consider the utilization of the nuclear genome, while less attention is given to plastid and mitochondrial genomes. The objective of this review is to present current knowledge about cytoplasmic and cytonuclear effects on agronomic traits bearing in mind the prospective utilization of all the genomes in plant breeding.